Rehabilitation of 'degraded Coppice Sal' Forests Vis-a-vis Conversion to Eucalyptus Plantations in South Bengal - a Financial Study - Sanyal, P. (Indian Forester, 1975)
Bulk supply of mining pit props and constructional poles come from the coppice sal forests of dry lateritic tracts. Owing to pressure of population at fringes such forests are often found in a state of degradation, being gradually replaced by miscellaneous scrubs. While tackling such areas by complete conversion to pulpwood plantation (Eucalyptus), it has become expedient to determine the stage of degradation in order to justify the same on economic grounds. A rough financial index for field foresters has been derived by comparing the profitability of Euacalyptus plantations vis-a-vis rehabilitation the degraded sal coppice forests. Thus for allocating areas to Pulp-wood Working Circle in Quality I, II and III sites of Eucalyptus, the existing coppice forests should contain less than 328, 215 and 162 numbers of viable sal tools per ha, respectively. If the density is more the sal coppice crop will give a better return.